A 2020 Update on 20/20 X 2: Diplopia after Glaucoma Surgery. Issue 4 (2nd October 2021) - Capó, Hilda
ABSTRACT: New-onset diplopia is an important complication that may occur following several types of ocular surgery, including glaucoma surgery. Surgeons should be aware of the possibility of ocular motility disturbances after glaucoma surgery, whereas strabismus experts must understand the mechanisms and the most appropriate management of these forms of strabismus. The incidence, mechanisms, characteristics and treatment of diplopia and strabismus after glaucoma surgery will be reviewed.